ChemInform Abstract: Nanocast Mesoporous Mixed Metal Oxides for Catalytic Applications. Issue 38 (10th September 2014) - Nair, Mahesh Muraleedharan; Yen, Hoang; Kleitz, Freddy
Abstract Review: 113 refs.